Determinants of turnover intentional in Islamic Bank Institution - Desthiani, Unik; Ratna Suminar (Annals of Human Resource Management Research, 2025)
Purpose: The objective of this study is to investigate the impact of job uncertainty and job stress on turnover intentions, with a focus on employees of Islamic Banking Institutions. The aim is to provide insights into how to reduce turnover through Islamic organizational principles, as this aligns with the research theme. Methodology: A quantitative descriptive approach was used, involving 31 employees from various divisions in Islamic Banking Institutions. Data collection was conducted through questionnaires and documentation. Smart PLS (Partial Least Squares) was employed for structural equation modeling, and regression analysis was used for hypothesis testing. Results: The results indicate that job insecurity does not significantly influence turnover intention, while job stress has a substantial impact. Combined, these factors significantly affect turnover intention. Islamic economic principles, such as fairness and employee welfare, play a critical role in addressing these issues. Conclusions: Turnover intention in Islamic banks is more strongly driven by stress factors than by insecurity. Aligning HR practices with Islamic economic principles such as equitable treatment, workload balance, and employee well-being can reduce stress, increase loyalty, and enhance workforce stability. Limitations: The study is limited to one organization, restricting generalizability. Future research could include other Islamic banks or financial institutions for broader insights. Contribution: This research contributes theoretically by integrating Behavioral Accounting Theory with Islamic economic principles to explain turnover intention. Practically, it provides actionable insights for HR managers in Islamic banks to design stress-reduction policies and employee support systems that foster retention and align with Sharia-based organizational values.